DETERMINAN JUMLAH LIMBAH KOTA YANG DIHASILKAN DARI SEMBILAN NEGARA EKONOMI BERKEMBANG DI ASIA TAHUN 2010-2017 - Lia Khairunnisak; Timbang Sirait (Politeknik Statistika STIS, 2020)
municipal waste is a serious problem that must be faced by all countries in the world. Increasing the amount of municipal waste every year is also in line with the development of urban areas in a country. Municipal waste generated by each country is found to be increasing rapidly in countries with developing economies. Asia is known as the largest waste-producing continent in the world, where most of the developing countries are known to be the largest contributors to the total waste generated from the entire world. The data used are data from nine developing economies that were selected using a classification from UNCTAD based on the status of development (Indonesia, Malaysia, China, Kyrgyzstan, Kazakhstan, Azerbaijan, Armenia, Turkey, Singapore). The purpose of this study is to determine the factors that influence the amount of municipal waste generated in nine selected developing economies in Asia. The analytical method used is panel data regression analysis (fixed effect-weight least square (FEM-WLS)) . The analysis shows that the variable number of urban population and Foreign Direct Investment (FDI) significantly influence the amount of municipal waste generated by the nine selected developing economies.